Efficient activation of peroxymonosulfate by magnetic Mn-MGO for degradation of bisphenol A - Du, Jiangkun; Bao, Jianguo; Liu, Ying; Ling, Haibo; Zheng, Han; Kim, Sang Hoon; Dionysiou, Dionysios D. (ELSEVIER SCIENCE BV, 2016)
A heterogeneous manganese/magnetite/graphene oxide (Mn-MGO) hybrid catalyst was fabricated through the reduction of KMnO4 by ethylene glycol in the presence of magnetite/GO (MGO) particles. The Mn-MGO catalyst exhibited high efficacy and long-term stability in activating peroxymonosulfate (PMS) to generate sulfate radicals for the removal of bisphenol A (BPA) from water. The results of the batch experiments indicated that an increase in the catalyst dose and solution pH could enhance BPA degradation in the coupled Mn-MGO/PMS system. Regardless of the initial pH, the solution pH significantly dropped after the reaction, which was caused by catalytic PMS activation. The production of sulfate radicals and hydroxyl radicals was validated through radical quenching and electron paramagnetic resonances (EPR) tests. BPA degradation pathways were proposed on the basis of LC-MS and GC-MS analyses. Finally, a possible mechanism of catalytic PMS activation was proposed that involved electron transfer from MnO or Mn2O3 to PMS with the generation of sulfate radicals, protons and MnO2, as well as the simultaneous reduction of MnO2 by PMS. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: ENDOCRINE DISRUPTING COMPOUNDS; CATALYTIC PHENOL DEGRADATION; ADVANCED OXIDATION PROCESSES; WASTE-WATER TREATMENT; SULFATE RADICALS; HETEROGENEOUS CATALYSTS; AQUEOUS-SOLUTIONS; ORGANIC POLLUTANTS; GRAPHENE OXIDE; COMPOUNDS EDCS